The Influence of Self-Efficacy and Entrepreneurship Education on Entrepreneurship Interest of Economic Education Students - Jamilatun, Putri; Haryanto, Dwi; Rezki, Istighfaris; Jailani, Muhammad; Setiawan, Muhammad Andi (International Journal of Universal Education, 2023)
The objectives of this study are: (1) Explain the effect of self-efficacy on the entrepreneurial interest of Economic Education students. (2) Explain the influence of entrepreneurship education on the entrepreneurial interest of Economic Education students. (3) Explain the influence of self-efficacy and entrepreneurship education on the entrepreneurial interest of Economic Education students. To achieve the above objectives, a quantitative research approach with a descriptive type of research is used. The instrument used is in the form of a questionnaire, Instrument testing uses validity and reliability tests. While the data analysis method uses multiple linear regression, with a total of 98 students. The results of the research that have been carried out can be concluded that: (1) The Self-Efficacy Variable has a t count of 3.375 which is greater than the table t value of 0.67705 with a significance value of 0.001 smaller than 0.05. In accordance with this description, it can be concluded that Self-Efficacy affects Entrepreneurial Interest. (2) The variable of Entrepreneurship Education has a t count of 2.296 which is greater than the table t value of 0.67705 with a significance value of 0.024 smaller than 0.05. In accordance with this description, it can be concluded that Entrepreneurship Education affects Entrepreneurial Interest. (3) The results of the analysis on the third hypothesis test show that the calculated F value has a value of 18.012 where the calculated F value of the variable is greater than the table F which is 3.092 and has a significance probability value of 0.000 where the value is smaller than 0.05